2019
DOI: 10.1136/bmj.l5274
|View full text |Cite
|
Sign up to set email alerts
|

Immediate impact of minimum unit pricing on alcohol purchases in Scotland: controlled interrupted time series analysis for 2015-18

Abstract: Objective To assess the immediate impact of the introduction of minimum unit pricing in Scotland on household alcohol purchases. Design Controlled interrupted time series analysis. Setting Purchase data from Kantar Worldpanel’s household shopping panel for 2015-18. Participants 5325 Scottish households, 54 807 English households as controls, and 10 040 households… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
192
3
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(213 citation statements)
references
References 47 publications
15
192
3
3
Order By: Relevance
“…While effective and cost-effective policies already do exist to reduce alcohol-attributable burden [67][68][69], two additional considerations should be focused on: first, each measure must be examined to ensure it does not widen the gap between socioeconomic strata and, second, the measures should target heavy drinking occasions. Thus, in addition to the raising taxes on alcohol, restricting its availability, and banning its advertisement, the current "best buys" for alcohol control-measures such as minimum pricing per unit-should be considered, as they have shown to have a strong effect on the drinking behaviour of heavy drinkers in lower socioeconomic strata [70].…”
Section: Discussionmentioning
confidence: 99%
“…While effective and cost-effective policies already do exist to reduce alcohol-attributable burden [67][68][69], two additional considerations should be focused on: first, each measure must be examined to ensure it does not widen the gap between socioeconomic strata and, second, the measures should target heavy drinking occasions. Thus, in addition to the raising taxes on alcohol, restricting its availability, and banning its advertisement, the current "best buys" for alcohol control-measures such as minimum pricing per unit-should be considered, as they have shown to have a strong effect on the drinking behaviour of heavy drinkers in lower socioeconomic strata [70].…”
Section: Discussionmentioning
confidence: 99%
“…Such a conclusion would suggest the need for the introduction of effective alcohol policies—to at the very least not increase the affordability of alcohol as has been the tendency over the past decades (Kerr et al, ). This could be achieved via alcohol taxation increases and—in the event that decision makers shy away from such measures for fear of losing votes or for other reasons—through the implementation of minimum unit prices for alcohol, the introduction of which has recently been shown to be particularly effective for heavy alcohol consumers in lower socioeconomic strata (O'Donnell et al, ), the strata most highly affected by recent increases in alcohol‐related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…KWP is a longitudinal panel of approximately 30 000 households recruited using stratified sampling to be representative of the population of Great Britain in relation to region, household size, age of main shopper and socioeconomic status, who use barcode scanners to scan receipts for all online and off-line purchases brought into the home (non-barcode purchases can also be included). More details of the dataset have been provided elsewhere [8,9]. For this study we had access to the 11 695 households who provided data indicating that they had purchased cigarettes, RYO tobacco, cigars/cigarillos and pipe tobacco, electronic cigarettes (ecigarettes) and nicotine replacement therapy (NRT).…”
Section: Data Sources and Research Designmentioning
confidence: 99%
“…However, our results on purchase and price trends for legal pack sizes presented here have shown that even though consumers switched to bigger pack size cigarette products, they paid a lower average price per cigarette, closer to that of the 11 to 19 cigarette packs available before the new policy was implemented, by moving down by one price quartile to cheaper products. We recognize that Nielsen Scantrack data are more comprehensive in terms of the number of products included [8], but KWP is representative of consumers' purchasing behaviour. Trends in prices by price quartile observed in this study were consistent with those observed in studies using alternative methods for price segmentation [3,10,17].…”
Section: Consumer's Choice After Plain Packagingmentioning
confidence: 99%